2000
DOI: 10.1021/bi000985x
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the Actomyosin Complex by Negative Charges on Myosin

Abstract: Sequence comparisons of members of the myosin superfamily show a high degree of charge conservation in a surface exposed helix (Dictyostelium discoideum myosin II heavy chain residues S510 to K546). Most myosins display a triplet of acidic residues at the equivalent positions to D. discoideum myosin II residues D530, E531, and Q532. The high degree of charge conservation suggests strong evolutionary constrain and that this region is important for myosin function. Mutations at position E531 were shown to strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 25 publications
3
43
0
Order By: Relevance
“…Kinases are known to prefer phosphorylation of less well ordered and surface-exposed regions of proteins (17), which is consistent with studies that demonstrate loop 2 is highly disordered in myosins (46). Studies have demonstrated that the degree of positive charge in loop 2 can impact actin-activated ATPase activity and actin affinity of myosins (47)(48)(49). The additional negative charges associated with phosphorylation are well positioned to reduce actin affinity and ATPase activity.…”
Section: Discussionsupporting
confidence: 80%
“…Kinases are known to prefer phosphorylation of less well ordered and surface-exposed regions of proteins (17), which is consistent with studies that demonstrate loop 2 is highly disordered in myosins (46). Studies have demonstrated that the degree of positive charge in loop 2 can impact actin-activated ATPase activity and actin affinity of myosins (47)(48)(49). The additional negative charges associated with phosphorylation are well positioned to reduce actin affinity and ATPase activity.…”
Section: Discussionsupporting
confidence: 80%
“…We also confirm the interaction of loop 3 with two actin monomers (34,35), which are among the initial weak actin-binding interactions. Structural and mutational studies indicate that dynamic interactions of loop 2 with different regions of actin in the different states of actomyosin reflect its role in the weak to strong actin-binding transition of myosin (36,37). We found that loop 2 positioned differently in rigor compared with the weak actinbinding state.…”
Section: Discussionmentioning
confidence: 66%
“…a high stiffness, no power stroke state). Such interactions were first detected in relaxed skinned muscle fibers which were oscillated at high frequency (53) and were later proposed to arise from nonspecific ionic interactions between loop II of myosin with actin (54). Such interactions were predicted to be the basis for the ability of unphosphorylated smooth muscle myosin to retard the movement of actin filaments by phosphorylated smooth muscle myosin in in vitro actin gliding motility assays (55).…”
Section: Attachment Modementioning
confidence: 99%